Analisis Resentralisasi Sebagai Kemunduran Otonomi Daerah Di Indonesia - Sitti Mutmainnah Syam (Universitas Musamus, 2024)
Decentralization has become an agenda in response to the hopes of the people who want equitable development results for all Indonesian people. The implementation of decentralization is the result of a long struggle for democracy, starting from the Dutch colonial era which implemented centralized government to the reform phase which made decentralization the main agenda for equitable development. However, several recentralization policies after decentralization have produced many positive results in the implementation of development, therefore this research outlines the forms of recentralization which indicate a decline in the implementation of regional autonomy and a decline in regional autonomy and decentralization in accelerating regional development. The research method used is normative legal research or what is known as doctrinal law or library legal research. The results of this research show that several regional authorities were taken over by the central government, such as the authority of regional governments in granting mining permits was eliminated. Changes in regulations regarding the authority to determine regional tax rates also narrowed the space for Regional Governments to manage their regions, as well as Special Autonomy for Papua as a grant. wider authority for the province and the Papuan people to regulate and manage themselves within the framework of the Republic of Indonesia, now some of its authority has been withdrawn to the center, the center can now bypass the regional government and the Papuan People's Assembly (MRP) in carrying out the expansion of the province. A number of these policies have the potential to reduce the initiative and creativity of regional governments and local communities. The shift from a centralized paradigm to decentralization which was fought for a long time to manage the country back to a centralized one due to the withdrawal of some of these authorities, the withdrawal of a number of authorities which were once given to the regions by the center is a setback in democracy in Indonesia.